Effect of Nitric Oxide on Seed Germination and Dormancy in Empress Trees - Jia Liu (HortTechnology, 2019)
Freshly harvested empress tree (Paulownia elongata) seeds have physiologic dormancy. The aim of this study was to investigate the effects of exogenous and endogenous nitric oxide (NO) on the dormancy and germination of empress tree seeds. After treatment with different concentrations of sodium nitroprusside (an NO-releasing compound) solution, the germination percentage of seeds under 12 h of continuous light was significantly greater. Seed germination percentage was promoted significantly by 10–4 M sodium nitroprusside plus cold stratification compared with seeds treated with cold stratification only. At different hours during imbibition, empress tree seeds treated with 2-(4-carboxyphenyl)-4, 4, 5, 5- tetramethylimidazoline -1-oxyl-3-oxide potassium salt (c-PTIO), NG-nitro-L-arginine methyl ester (L-NAME), and sodium tungstate showed reduced seed germination percentages. During the early hours of imbibition, c-PTIO or sodium tungstate treatment inhibited seed germination significantly. The results showed that both exogenous and endogenous NO can release empress tree seed dormancy. Endogenous NO oxide was involved in dormancy release and germination of seeds during the early stages of imbibition. Wider application of NO may be used for breaking seed dormancy in other species.